2017
DOI: 10.1097/jhq.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Therapist Productivity: Using Lean Principles in the Rehabilitation Department of an Academic Medical Center

Abstract: The Department of Rehabilitation Services, within the University of Maryland Medical Center's 650-bed academic medical center, was experiencing difficulty in meeting productivity standards. Therapists in the outpatient division believed they were not spending enough time performing billable patient care activities. Therapists in the inpatient division had difficulty keeping pace with the volume of incoming referrals. Collectively, these issues caused dissatisfaction among referral sources and frustration among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Half of the respondents reported productivity was assessed using both number of patients and billable units per day, whilst the remaining respondents stated that only utilised number of patients or billable units per day were assessed. This inconsistent approach to calculating productivity is reflected in the literature with productivity being reported as billable units, 19,20 number of treatments per hour, 20 day, 3 or week, 21 patient evaluations per hour, 20 percentage of billable time per day, 3 and patient visits per week. 21 With the CPI's dependence on clinical sites' new graduate caseload expectations and employers utilising a variety of metrics to assess productivity, it may be challenging to assess student caseload consistently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Half of the respondents reported productivity was assessed using both number of patients and billable units per day, whilst the remaining respondents stated that only utilised number of patients or billable units per day were assessed. This inconsistent approach to calculating productivity is reflected in the literature with productivity being reported as billable units, 19,20 number of treatments per hour, 20 day, 3 or week, 21 patient evaluations per hour, 20 percentage of billable time per day, 3 and patient visits per week. 21 With the CPI's dependence on clinical sites' new graduate caseload expectations and employers utilising a variety of metrics to assess productivity, it may be challenging to assess student caseload consistently.…”
Section: Discussionmentioning
confidence: 99%
“…These factors relate to student physical therapists' ability to manage time efficiently. Johnson et al 3 found it can be challenging for novice physical therapist clinicians to manage their workday to meet productivity standards and difficulty communicating has caused CIs to question students' ability to demonstrate ELP. 10 These findings support respondents consideration of efficiency factors as moderately important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation